Concentration and quantification of Tilapia tilapinevirus from water using a simple iron flocculation coupled with probe-based RT-qPCR - Taengphu, S.; Kayansamruaj, P.; Kawato, Y.; Delamare-Deboutteville, Jerome; Mohan, Chadag V.; Dong, H.T.; Senapin, S. (PeerJ, 2022)
Background Tilapia tilapinevirus, also known as tilapia lake virus (TiLV), is a significant virus that is responsible for the die-off of farmed tilapia across the globe. The detection and quantification of the virus using environmental RNA (eRNA) from pond water samples represents a potentially non-invasive and routine strategy for monitoring pathogens and early disease forecasting in aquaculture systems.